2014
DOI: 10.1210/en.2013-1993
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bisphosphonates on the Rapidly Growing Male Murine Skeleton

Abstract: Bisphosphonates are effective for preventing and treating skeletal disorders associated with hyperresorption. Their safety and efficacy has been studied in adults where the growth plate is fused and there is no longitudinal bone growth and little appositional growth. Although bisphosphonate use in the pediatric population was pioneered for compassionate use in the treatment of osteogenesis imperfecta, they are being increasingly used for the treatment and prevention of bone loss in children at risk of hyperres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 44 publications
5
33
0
2
Order By: Relevance
“…This observation is at odds with a study (32) (2.5 mg/kg ALN dose) showing a dose-dependent decrease in hypertrophic chondrocyte apoptosis. However, our finding is partly in agreement with a report (35) that showed a decrease in the number of hypertrophic chondrocytes per column, but no changes in vascular invasion or apoptosis rate (0.1 mg/kg ALN twice a week). It could be posited that higher doses of ALN might impair apoptosis increasing hypertrophic zone thickness, whereas lower doses would not.…”
Section: Discussionsupporting
confidence: 93%
“…This observation is at odds with a study (32) (2.5 mg/kg ALN dose) showing a dose-dependent decrease in hypertrophic chondrocyte apoptosis. However, our finding is partly in agreement with a report (35) that showed a decrease in the number of hypertrophic chondrocytes per column, but no changes in vascular invasion or apoptosis rate (0.1 mg/kg ALN twice a week). It could be posited that higher doses of ALN might impair apoptosis increasing hypertrophic zone thickness, whereas lower doses would not.…”
Section: Discussionsupporting
confidence: 93%
“…In growing wild-type mice, treatment with alendronate, pamidronate, and zoledronate led to a decrease in the number of chondrocytes in the hypertrophic chondrocyte layer. This was not associated with altered chondrocyte apoptosis or altered vascular invasion at the growth plate [16]. However, this may differ in OI.…”
mentioning
confidence: 73%
“…43 Other studies have demonstrated substantial increases in both cortical and trabecular bone with bisphosphonate treatments in young male mice. 21 Further investigation is needed into the sex-dependent effects of these drugs in pediatric models. Secondly, only one dosing strategy was evaluated in this study for each of the proof-of-concept drugs.…”
Section: Discussionmentioning
confidence: 99%
“…1820 In growing male mice, alendronate, zoledronic acid, pamidronate, and clodronate treatment resulted in substantial increases in cortical and trabecular bone mass, suggesting that bone strength could be improved, but changes in mechanical strength were not measured. 21 …”
Section: Introductionmentioning
confidence: 99%